Reading to learn in the content areas - Judy S Richardson (Wadsworth, 1990)
This book is organized into chapters. Chapters One discusses reseach and priciples of content area instruction. Chapter Two explains how to provide for an affective focus for reading to learn. Chapters Three and Four are the Preparation chapters. In them we show why anf how to determine and build reader background. Chapters Five and Six are the Assistance chapter. In them we show why and how to provide purposeful reading and develop comprehension. Chapter Seven is a Reflection chapter because it focuses on why and how to help readers yhink critically about their reading. Chapters Eight and Nine, on study skills, and Ten, on vocabulary, teach very important reading and thinking skills. We show how these skills can be used at all phases of the PAR framework. Chapters Eleven and Twelve are specialized chapters pertaining to the difficult challenges of developing classroom tests and working with students who are at risk of failuren